Respuesta :

Answer:

g = 0 or g = -1/2

Step-by-step explanation:

Solve for g:

8 g^3 - 2 g^2 = 2 g^3 - 5 g^2

Subtract 2 g^3 - 5 g^2 from both sides:

6 g^3 + 3 g^2 = 0

Factor g^2 and constant terms from the left hand side:

3 g^2 (2 g + 1) = 0

Divide both sides by 3:

g^2 (2 g + 1) = 0

Split into two equations:

g^2 = 0 or 2 g + 1 = 0

Take the square root of both sides:

g = 0 or 2 g + 1 = 0

Subtract 1 from both sides:

g = 0 or 2 g = -1

Divide both sides by 2:

Answer: g = 0 or g = -1/2